Stephens' Visual Basic programming 24-hour trainer - Stephens, Rod 1961- (Wiley Pub., 2011)
Annotation
Keywords: Visual Basic; Visual Basic (Computer program language); Microsoft Visual BASIC; Microsoft Visual BASIC (Computer software); Visual Basic (Langage de programmation); BASIC (Computer language)